KUALITAS PRODUK DALAM MENINGKATKAN KEPUASAN PELANGGAN PRODUK KOSMETIK WARDAH CABANG BANJARMASIN (STUDI KASUS PADA TOKO GUARDIAN Q-MALL BANJARBARU) - Angga Ifanka; Rizki Amalia Afriana (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2023)
The purpose of this study was to determine the product quality variables (performance, reliability, features, durability, suitability, and design) play a role in customer satisfaction of Wardah products and to determine product quality variables (performance, reliability, features, durability, suitability, and design), which has the biggest role in customer satisfaction for Wardah products. The method used in this research is descriptive. With this method, the writer can find out how far product quality influences customer satisfaction of Wardah cosmetic products for consumers. The results of the research show that the problem with the Guardian Q-Mall Banjarbaru Store is that so far Wardah products have experienced a decline in sales due to the quality of the latest edition products which are still unknown and felt by customers and are dissatisfied with the quality of the latest edition of cosmetic products. In conclusion, Guardian is a shop that has been engaged in providing services for the health and beauty needs of the Indonesian people since 1990 and has officially become part of PT Hero Supermarket. Based on the questionnaire, the variable form, accuracy and suitability, style, design are variables that play a role in consumer satisfaction. Based on the results of the answers whether Wardah products have a different form of packaging from other products, 82% of respondents answered No, the results provided by Wardah products were in accordance with consumer wishes, 74% of respondents answered No, Wardah products made consumers appear more confident, 58% of respondents answered No, Wardah products have attractive designs compared to other products, 64% of respondents answered No, and Wardah products were as expected, 54% of respondents said No.